The Influence of Teacher Competency on Student Learning Outcomes - Suharyanto H. Soro; Ferry Wibowo; M. Idris Wikarso; Lilis Widiawati; Maryam; Nesa Halimah Adzani (Didaktika: Jurnal Kependidikan, 2024)
This research was motivated by the low cognitive learning outcomes of students at SD Rancamanyar 03 Bandung. The aim of this research is to determine and analyze whether there is an influence of teacher competence on students' cognitive learning outcomes at SD Rancamanyar 03 Bandung. This research uses a quantitative approach, descriptive method, data collection techniques using questionnaires and observation. Several statistical data analysis procedures that will be carried out include: Instrument Analysis (data validity and data reliability), Classic Assumption Test, namely: Data Normality Test, Data Linearity Test, Hesterocedasticity Test. And Statistical Analysis, namely Simple Linear Regression Analysis, Correlation Coefficient Analysis, Descriptive Statistical Analysis and Hypothesis Testing t Test. The results of this research indicate that teacher competency has a significant impact on student cognitive learning outcomes. This is based on the results of statistical testing with SPSS on teacher competency, the calculated t value = 2.210 > 2.035 = t table, and Sig. = 0.03 < 0.05 (5%), so Ho is rejected and H_a is accepted. These data show that teacher competence has a significant effect on student cognitive learning outcomes.